2004
DOI: 10.2165/00129784-200404030-00003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Prevention of Reperfusion Injury in Acute Myocardial Infarction

Abstract: The concept of reperfusion injury, although first recognized from animal studies, is now recognized as a clinical phenomenon that may result in microvascular damage, no-reflow phenomenon, myocardial stunning, myocardial hibernation and ischemic preconditioning. The final consequence of this event is left ventricular (LV) systolic dysfunction leading to increased morbidity and mortality. The typical clinical case of reperfusion injury occurs in acute myocardial infarction (MI) with ST segment elevation in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 104 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…Some of the agonists that may confer cardio protection include the use of adenosine, verapamil and nitric oxide, in contrast there is controversy in the role of some cytokines such as bradykinin, tumor necrosis factor alpha and IL-6 [12,19]. Signaling pathways include the opening of the sarcolemma and/or Mitochondrial ATP-Dependent Potassium Channels, and the activation of kinase (AKT and ERK-1/2, protein kinase C and G) blocking the final pathway of Mitochondrial transition [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the agonists that may confer cardio protection include the use of adenosine, verapamil and nitric oxide, in contrast there is controversy in the role of some cytokines such as bradykinin, tumor necrosis factor alpha and IL-6 [12,19]. Signaling pathways include the opening of the sarcolemma and/or Mitochondrial ATP-Dependent Potassium Channels, and the activation of kinase (AKT and ERK-1/2, protein kinase C and G) blocking the final pathway of Mitochondrial transition [18].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical complications occurred more frequently in group II. The Some strategies have been used to reduce reperfusion injury such as use of adenosine [12] and thrombus aspiration [13]. However, pathophysiology is complex and mechanisms to attach appropriate therapies has not been clearly established.…”
Section: Introductionmentioning
confidence: 99%
“…10 At an organ level, adenosine preserves postischaemic coronary flow reserve, coronary blood flow and postischaemic regional contractility. 11 It also reduces the accumulation of neutrophils in the area at risk. 11 In the present study, intravenous adenosine reduced reperfusion injury, improved myocardial perfusion and provided cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
“…11 It also reduces the accumulation of neutrophils in the area at risk. 11 In the present study, intravenous adenosine reduced reperfusion injury, improved myocardial perfusion and provided cardioprotection. These findings are in agreement with a previous study with intracoronary adenosine that reported improved myocardial perfusion and cardiac function in AMI patients undergoing selective PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine itself is used as a therapeutic agent for the treatment of supraventricular paroxysmal tachycardia and arrhythmias and, as a vasodilatatory agent, in cardiac imaging [46,47]. Two adenosine products, Adenocard® and Adenoscan®, have been approved by FDA and are currently available for cardiac arrhythmias treatment and for cardiac imaging, respectively [48,49].…”
Section: Adenosine Receptors As Therapeutic Targetsmentioning
confidence: 99%